Comparison of degradation behavior and osseointegration of 3D powder-printed calcium magnesium phosphate cement scaffolds with alkaline or acid post-treatment - Kowalewicz, Katharina; Waselau, Anja-Christina; Feichtner, Franziska; Schmitt, Anna-Maria; Brückner, Manuel; Vorndran, Elke; Meyer-Lindenberg, Andrea (Frontiers in Bioengineering and Biotechnology, 2022)
Due to the positive effects of magnesium substitution on the mechanical properties and the degradation rate of the clinically well-established calcium phosphate cements (CPCs), calcium magnesium phosphate cements (CMPCs) are increasingly being researched as bone substitutes. A post-treatment alters the materials’ physical properties and chemical composition, reinforcing the structure and modifying the degradation rate. By alkaline post-treatment with diammonium hydrogen phosphate (DAHP, (NH4)2HPO4), the precipitation product struvite is formed, while post-treatment with an acidic phosphate solution (e. g. phosphoric acid (PA, H3PO4)) results in precipitation of newberyite and brushite. However, little research has yet been conducted on newberyite as a bone substitute and PA post-treatment of CMPCs has not been described in the accessible literature so far. Therefore, in the present study, the influence of an alkaline (DAHP) or acid (PA) post-treatment on the biocompatibility, degradation behavior, and osseointegration of cylindrical scaffolds (h = 5.1 mm, Ø = 4.2 mm) produced from the ceramic cement powder Ca0.75Mg2.25(PO4)2 by the advantageous manufacturing technique of three-dimensional (3D) powder printing was investigated in vivo. Scaffolds of the material groups Mg225d (DAHP post-treatment) and Mg225p (PA post-treatment) were implanted into the cancellous part of the lateral femoral condyles in rabbits. They were evaluated up to 24 weeks by regular clinical, X-ray, micro-computed tomographic (µCT), and histological examinations as well as scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) analysis and compared with tricalcium phosphate (TCP). All materials showed excellent biocompatibility and rapid osseointegration. While TCP degraded only slightly, the CMPCs showed almost complete degradation. Mg225d demonstrated significantly faster loss of form and demarcability from surrounding bone, scaffold volume reduction, and significantly greater degradation on the side towards the bone marrow than to the cortex than Mg225p. Simultaneously, numerous bone trabeculae have grown into the implantation site. While these were mostly located on the side towards the cortex in Mg225d, they were more evenly distributed in Mg225p and showed almost the same structural characteristics as physiological bone after 24 weeks in Mg225p. Based on these results, the acid post-treated 3D powder-printed Mg225p is a promising degradable bone substitute that should be further investigated.